ANALISIS LAMA PEMAKAIAN KB SUNTIK DEPO MEDROXY PROGESTERON ACETATE DENGAN PENINGKATAN BERAT BADAN - Mella Yuria R.A; Irwanti Gustina; Legina Anggraeni (Universitas Batam, 2022)
Indonesia has a population problem with a population of approximately 250 million people. Approximately 34.3% of women of childbearing age in Indonesia mostly use cyclofem injection contraception and DMPA as a contraceptive method of choice. Weight gain, depression, disturbances in the menstrual cycle, depression, fluor albus, acne are some of the side effects caused by the use of DMPA contraception. This study aims to analyze the relationship between duration of use of DMPA injectable contraception and weight gain in WUS. design in this study was cross sectional, sample was determined using purposive sampling technique and the sample used was 50 WUS respondents. e time of the study was carried out in January-August 2021. data were analyzed using univariate and bivariat analysis using the Chi-square test. results showed that as many as 66% of DMPA injection family planning acceptors with a period of use > 24 months experienced an increase in body weight of 1-8 kg with a p-value of 0.001. From this study, it can be concluded that there is a relationship between duration of use of DMPA contraception to increase in WUS weight. DMPA acceptors who have used the contraceptive for > 24 months can increase the hormone progesterone which has an effect on increasing appetite. For this reason, it is recommended for acceptors who have used DMPA for a period of > 24 months to be able to regulate a balanced diet and nutrition as well as physical activities or sports.